Microstructural and crystallographical study of carbides in 30wt.%Cr cast irons - Wiengmoon A. (2014)
The microstructure and crystallography of carbides in 30wt.%Cr-2.3wt.%C cast irons with up to 3.7wt.%V additions have been studied by scanning electron microscopy and transmission electron microscopy. In a 30%Cr-2.3%C iron with no vanadium addition it was found that after destabilisation, M23C 6 secondary carbides were precipitated within the prior austenite dendritic matrix and that duplex core-shell structures were formed in the eutectic carbides. The M23C6 secondary carbide possessed the Kurdjumov-Sachs orientation relationship with the martensite matrix suggesting a possible cube-cube orientation relationship between the M 23C6 carbide and the austenite matrix with 〈1 1 0〉M23C6//〈1 1 0〉γ growth direction. The thickening of secondary carbide rods appeared to occur by the translation of steps on {1 1 1} planes in 〈1 1 2〉 directions. Vanadium additions to the 30%Cr-2.3%C cast irons produce ferritic matrix structures. Increasing the V content gave finer eutectic carbide structures, and also increased the volume fraction of eutectic carbides, which was in the range of 20-26%. The eutectic carbides in vanadium containing alloys had the stoichiometry Fe (1.6-1.8)Cr(4.9-5.7)V(0.7-1.3)C3. These eutectic carbides possessed an orientation relationship with the ferrite matrix close to {0 2 2 1}M7C3//{3 1 0}ferrite, {1 1 2 0}M7C3//{1 1 2}ferrite, 〈1 1 0 2〉M 7C3//〈1 3 1〉ferrite. © 2005 Acta Materialia Inc. Published by Elsevier Ltd. All rights reserved.